Evaluation of Land Suitability for Oil Palm Plantations in Gunung Tuleh District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study was to determine the suitability of oil palm plants in the Gunung Tuleh sub-district and overlay mapping of the suitability level of oil palm plants. The technique used is scoring analysis to provide an assessment of each land unit, the data used is secondary data processed from soil type map data. rainfall maps, slope maps, elevation maps, land use maps, geomorphological maps and river distance maps. Based on the results of map overlays or a combination of several land suitability maps in Tuleh Mountain, it is classified into 4 classifications namely; 1) not suitable (S1) has an area area around 23547.02 ha; 2) very suitable (S2) has an area of ​​10462.06 ha; 3) quite suitable (S3) has an area of ​​5245.81 ha; 4) According to the marginal area, it has an area of ​​9915.20 ha. So planting oil palm in Gunung Tuleh is not all areas that can be planted with oil palm because it has to consider the assessment of the valuation of a land so that the results of oil palm fruit production are maximized.